2019
DOI: 10.1021/acs.energyfuels.9b02821
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Oxyfuel Combustion in Lean-Premixed Multihole Burners

Abstract: This paper presents the results of an experimental investigation of combustion characteristics of nonswirl CH4/CO2/O2 flames under atmospheric pressure in a lean-premixed multihole burner’s gas-turbine model combustor. The CO2 and O2 are well premixed and then channeled to a test rig, which is made up of a 2 in. diameter 1 m long pipe to premix the fuel and oxidizers before getting to the multihole burner. The burner consists of main holes and subholes that prevent flashbacks that may lead to rig explosion. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
(57 reference statements)
2
11
0
Order By: Relevance
“…At same T ad , the C 3 H 8 /O 2 /CO 2 flames were found experimentally to have similar shapes with similar temperature profile near the flame core. This effect of T ad F I G U R E 2 Combustor mesh adopted in the developed numerical model [Colour figure can be viewed at wileyonlinelibrary.com] on flame macrostructure and combustor stability was observed in previous experiments on oxy-methane combustion in a swirl-stabilized burner 19,[52][53][54] and also in micromixer (MM) burner. 53,55 A set of pints within the stable combustion region was selected to present the change in flame shapes in different OF, ϕ, and T ad .…”
Section: Validation Of the Developed Modelmentioning
confidence: 66%
See 2 more Smart Citations
“…At same T ad , the C 3 H 8 /O 2 /CO 2 flames were found experimentally to have similar shapes with similar temperature profile near the flame core. This effect of T ad F I G U R E 2 Combustor mesh adopted in the developed numerical model [Colour figure can be viewed at wileyonlinelibrary.com] on flame macrostructure and combustor stability was observed in previous experiments on oxy-methane combustion in a swirl-stabilized burner 19,[52][53][54] and also in micromixer (MM) burner. 53,55 A set of pints within the stable combustion region was selected to present the change in flame shapes in different OF, ϕ, and T ad .…”
Section: Validation Of the Developed Modelmentioning
confidence: 66%
“…This effect of T ad F I G U R E 2 Combustor mesh adopted in the developed numerical model [Colour figure can be viewed at wileyonlinelibrary.com] on flame macrostructure and combustor stability was observed in previous experiments on oxy-methane combustion in a swirl-stabilized burner 19,[52][53][54] and also in micromixer (MM) burner. 53,55 A set of pints within the stable combustion region was selected to present the change in flame shapes in different OF, ϕ, and T ad . Figure 5 depicts the side-view images of the flames at fixed OF of 60% (A-E), fixed ϕ of 0.5 (F-J), and fixed T ad of 2302 K (K-P).…”
Section: Validation Of the Developed Modelmentioning
confidence: 66%
See 1 more Smart Citation
“…Badra et al 92 have proposed a combustor design based on the MM concept but for nonpremixed flames, which can preheat the fuel and oxidizer using the heat from the combustion products. Aliyu et al 93 have performed one of the first studies of oxy-fuel combustion using a MM-like burner. They have reported that the main parameter controlling flame stability and structure is the adiabatic flame temperature (T ad ), as observed in Figure 17.…”
Section: Micromixer (Mm) Burnersmentioning
confidence: 99%
“…Figure 17. Stability map of a MM-like oxy-fuel combustor operating at fixed jet velocity, plotted against the contours of a constant adiabatic flame temperature 93. …”
mentioning
confidence: 99%